PENGARUH KUALITAS PRODUK DAN KUAITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA SCUTI COFFEE CAFE DI CIGANJUR JAKARTA SELATAN - Ahmat Barji Meturan; Fauziah Septiani (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of product quality and service quality on customer satisfaction at Scuti Coffee cafe in Ciganjur, South Jakarta. This research method uses associative research with a quantitative approach.. The sampling technique used the rao purba formula and obtained a sample of 96 respondents. Data processing and analysis techniques use instrument tests, classical assumption tests, linear regression tests, correlation coefficient tests, determination tests, and hypothesis testing. Based on research conducted that the results of Product Quality (X1) and Service Quality (X2) have a significant effect on Customer Satisfaction (Y) with the regression equation value Y = 7.081 + 0.643 X1 + 0.159 X2 + a. The coefficient of determination simultaneously affects 45%. Partial hypothesis testing the product quality number is t count> t table or (8.502> 1.660) this is also reinforced by a significance value of 0.000 <.0.05. Thus, Ho1 is rejected and Ha1 is accepted. This means that partially there is a positive and significant influence between the Product Quality variable (X1) on Customer Satisfaction (Y). Service quality is tcount> t table or (3.400> 1.660) this is also reinforced by a significance value of 0.000 <0.05. Thus, Ho2 is rejected and Ha2 is accepted, meaning that partially there is a positive and significant influence between the Service Quality variable (X2) on Customer Satisfaction (Y). Hypothesis testing obtained the value Fhitung> Ftabel or (38.019> 3.09), thus Ho3 is rejected and Ha3 is accepted. This means that there is a simultaneous positive and significant influence between the variables of Product Quality (X1) and Service Quality (X2) on Customer Satisfaction (Y).